The Struggles to Overcome Traumatic Deviant Sexual Abuses as Starkly Portrayed in “Funeral Rites” by Jack Dickson - Ratna Asmarani; Inni Inayati Istiana; Tri Wahyuni (Balai Bahasa Sulawesi Selatan, 2024)
The short story titled